Pengembangan Media Pembelajaran Kartu Bergambar Berbasis Qr Code pada Mata Pelajaran PAI Materi Asma’ul Husna untuk Siswa kelas V SD/MI - Suri, Dharlinda; Hidayat, Nurdin; Putri, Dama Azzahra (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2025)
The problems in this study are: 1) The unavailability of learning media, especially in Islamic Religious Education (PAI) subjects. 2) Educators focus on textbooks. 3) The teaching method is conventional. 4) There is no use of Qr Code-based Picture Card learning media, especially in Islamic Religious Education (PAI) subjects. This study aims to develop, test the feasibility, and the response of students and educators to the Qr Code-based Picture Card media for Islamic Religious Education subjects with the material Closer to the Names of Allah (Asma'ul Husna) for fifth-grade students of SD Negeri 1 Pinang Jaya. This study uses the ADDIE model with five stages, namely (Analysis, Design, Development, Implementation and Evaluation). The Qr Code-based picture card media was validated by material experts, media experts and linguists. Then the revised Qr Code-based picture card media was tested to determine the responses of educators and students. The results of the validation by material experts obtained an average score of 92%, the results of the validation by media experts with an average score of 96%, while the results of the validation by linguists with an average score of 98%. From the three expert validators, the Qr Code-based picture card media with the interpretation criteria is "very feasible". The educator's response obtained an average score of 95%, and the student's response obtained an average score of 92% with the interpretation criteria "very interesting". The development of the Qr Code-based Picture Card media for the PAI subject with the material Closer to the Names of Allah (Asma'ul Husna) for grade V elementary school students using the Research and Development (R&D) research method, it can be concluded that the use of the Qr Code-based Picture Card media for the PAI subject with the material Closer to the Names of Allah (Asma'ul Husna) is very feasible and effective to use as a learning medium.